AN ATTORNEY’S LEGAL DUTY TOWARDS A THIRD PERSON Road Accident Fund v Shabangu 2005 1 SA 265 (SCA) - Rian Cloete; Llewelyn Gray Curlewis (Obiter, 2022)
The recent decision in Road Accident Fund v Shabangu (2005 1 SA 265 (SCA)) has prompted us to revisit the attorney’s legal duty towards a third person. In this matter the respondents were a firm of attorneys. They lodged a claim with the Road Accident Fund (RAF) for compensation in terms of the Multilateral Motor Vehicle Accidents Fund Act 93 of 1989 on behalf of a client who pretended to be the widow, and mother of the children, of a man who she said had died in a collision between two motor vehicles. The Fund settled the claim and the respondents, duly instructed by the client, signed a discharge form. The settlement amount was paid into the account of the respondents and was dealt with thereafter in accordance with the instructions of the client. It later appeared that the client was an impostor and that in fact even the deceased’s dependants had no claim against the Fund, since no other vehicle had been involved in the accident which caused his death.The Fund pursued its claim on a number of bases. In this note, however, we shall focus only on the attorney’s negligence in failing to ascertain the true identity of their client when they submitted the claim. The question is whether the act or omission relied upon was wrongful, that is, whether the respondents owed a legal duty to the Fund; for if they did not, they would not be liable to the Fund and the inquiry into negligence does not arise.Despite the court’s finding that the respondents had no such legal duty, it is submitted that the decision did not open the door for practitioners to act recklessly.